Evaluate how steaming and sulfur fumigation change the microstructure, physicochemical properties and in vitro digestibility of Gastrodia elata Bl. starch - Guan, Jinjie; Chen, Zhuowen; Guo, Lanping; Cui, Xiuming; Xu, Tingting; Wan, Fen; Zhou, Tao; Wang, Chengxiao; Yang, Ye (Frontiers in Nutrition, 2023)
Sulfur is an important industrial raw material. The sulfur dioxide gas (SO2) generated after burning can significantly improve the appearance quality of food and enhance the storage time. However, excessive sulfur dioxide will not only pollute the environment, but also cause the deterioration of food quality, and even the high residual levels can increase the risk of cancer. Traditional processing technology for Gastrodia elata Blume is designed to steam fresh G. elata, followed by fumigation with sulfur, and then dried. However, the effect of this technology on the edible quality of G. elata and its mechanism have yet to be investigated. Starch is the main component of G. elata, which has a significant impact on its morphology and chewiness. Therefore, the effects of traditional processing technology on the morphology, chewiness, and structure of G. elata starch were investigated via spectral analysis and Texture Profile Analysis (TPA). The results showed that compared with G. elata non-steam and non-sulfur fumigation (NSt-NSf), the pH of G. elata after steam and sulfur fumigation (St-Sf) decreased by 0.399, and the starch whiteness, paste transparency and amylose content increased by 1.15-fold, 1.08-fold and 1.10-fold, respectively (p < 0.05). The solubility of starch was reduced by 70%, the swelling degree, starch gel chewiness and the content of rapidly digested starch were increased by 1.66-, 1.17-, and 1.09-fold, respectively. The final viscosity of starch was increased by 5.22-fold (p < 0.05). After steaming, the starch granules form a smooth surface, but the surface of starch granules after sulfur fumigation can see obvious erosion traces, and the starch after sulfur fumigation is easier to gelatinize into a homogeneous solution and improve the cross-linking between molecules. To sum up, sulfur fumigation after steaming (St-Sf) promote the increase of amylose content and the release of molecular chains from starch granules, which are the main reasons for improving the morphology and chewiness of G. elata starch. This study can provide technical and theoretical support for improving the quality of starch-rich foods, replacing sulfur fumigation and reducing potential environmental hazards.